Granulocyte/monocyte adsorptive apheresis for the treatment of therapy-refractory chronic active ulcerative colitis. (3rd April 2018) - Dignass, Axel; Akbar, Ayesha; Baumgart, Daniel C.; Bommelaer, Gilles; Bouguen, Guillaume; Cadiot, Guillaume; Gillessen, Anton; Grimaud, Jean-Charles; Hart, Ailsa; Hoque, Syed; Makins, Richard; Michiels, Christophe; et al.
Abstract: Objectives: Current options for patients with steroid-dependent, chronic-active ulcerative colitis (UC) with insufficient response/intolerance to immunosuppressants (ISs) and/or biologics are limited. The aim of this study was to assess the long-term outcome of granulocyte/monocyte adsorptive (GMA) apheresis (Adacolumn ® ) in this population. Materials and methods: Ninety five adults with steroid-dependent active UC and insufficient response/intolerance to IS and/or TNF inhibitors received 5–8 aphereses in a single induction series of ≤10 weeks. Endpoints included rates of remission (clinical activity index [CAI] ≤ 4) at weeks 24 and 48. Results: Of 94 patients (ITT population), remission and response rates were 34.0% and 44.7% at week 24, and 33.0% and 39.4% at week 48. Among 30 patients with prior failure of IS and biologics, 33.3% and 20.0% were in remission at weeks 24 and 48. At both weeks, 19.2% of patients achieved steroid-free remission. Sustained remission or response occurred in 27.7% of patients at 48 weeks. The cumulative colectomy rate at week 96 was 23.4%. Safety was consistent with previous findings. Conclusions: This study confirms findings of the 12-week interim analysis and demonstrates that GMA apheresis provides a safe and beneficial long-term outcome for patients with chronic active UC resistant/intolerant to IS and/or TNF inhibitors.